2008
DOI: 10.1007/bf03007363
|View full text |Cite
|
Sign up to set email alerts
|

Reversible impairment of coronary flow reserve in takotsubo cardiomyopathy: A myocardial PET study

Abstract: The acute phase of takotsubo cardiomyopathy is characterized by an inverse perfusion/metabolism mismatch with a reduction in CFR in the apical segments. However, the impairment of CFR and the reduction of metabolism in the apical segments recovered completely after 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 25 publications
1
34
0
1
Order By: Relevance
“…Reversibility of MVD in this syndrome has been demonstrated non-invasively on Doppler transthoracic echocardiography 7 and positron emission tomography, 8 and invasively with intracoronary Doppler wire 9 in previous studies using CFR. IMR, however, is considered more useful to detect MVD because of the independence of epicardial stenosis and hemodynamic status, 10,11 but only 2 cases of MVD in takotsubo syndrome have been reported using IMR in the acute phase.…”
Section: Images In Cardiovascular Medicine Reversible Mvd In Takotsubmentioning
confidence: 80%
“…Reversibility of MVD in this syndrome has been demonstrated non-invasively on Doppler transthoracic echocardiography 7 and positron emission tomography, 8 and invasively with intracoronary Doppler wire 9 in previous studies using CFR. IMR, however, is considered more useful to detect MVD because of the independence of epicardial stenosis and hemodynamic status, 10,11 but only 2 cases of MVD in takotsubo syndrome have been reported using IMR in the acute phase.…”
Section: Images In Cardiovascular Medicine Reversible Mvd In Takotsubmentioning
confidence: 80%
“…Invasive studies (using TIMI frame counts, myocardial perfusion grading, intracoronary Doppler evaluation of vasomotor function, coronary flow reserve and thermodilution method to assess index of microvascular resistance) and noninvasive studies (using doppler echocardiography, myocardial contrast echocardiography, SPECT/PET metabolism/ perfusion and Cardiac MRI) have all demonstrated coronary microvascular dysfunction in the acute phase of takotsubo cardiomyopathy 5,7,[12][13][14][15][17][18][19][20][22][23][24][25][26][27][28]33 Of significance, all of these microvascular abnormalities demonstrated by both invasive and noninvasive testing usually are transient and reversible, with follow up testing indicating normalization of microvascular function, in parallel with recovery of LV function. The precise mechanism of this transient coronary microvascular dysfunction, although not completely understood, could involve adrenoreceptor overstimulation/sympathetic hyperactivity, resulting from a catecholamine surge secondary to physical or emotional stress and differences in the type and density of adrenoreceptors in the cardiac apex versus the base might partly explain the proclivity of transient apical dysfunction in TC.…”
Section: Resultsmentioning
confidence: 99%
“…3 In a study of 3 patients with TC, Feola et al evaluated myocardial perfusion and myocardial blood flow using PET imaging. 26 All 3 patients underwent coronary angiography at admission which ruled out significant coronary stenosis. PET perfusion imaging using N13 ammonia at rest and during pharmacologic stress with adenosine and metabolic imaging using FDG was done within 3 days of presentation and again at 3 months of follow up.…”
Section: Noninvasive Methods Of Cmvd Assessment -Pet Perfusion Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using 13 N-NH3 and hyperinsulinemic-euglycemic clamp prepped 18 F-FDG PET, Feola and colleagues showed reductions in both coronary flow reserve and glucose metabolism in the apical segments during the acute phase in 3 TC patients that recovered completely after 3 months. 25 During the acute phase, FDG uptake was severely reduced in the apical and mid-ventricular segments in all 3 patients, with only modest reductions in stress perfusion that normalized at rest (described as an inverse-mismatch of flow/metabolism). 25 The authors suggested a transient metabolic disorder at the cellular level from a microcirculation disturbance as the potential explanation of their findings.…”
Section: See Related Article Pp 1260-1270mentioning
confidence: 99%